Impact of mRNA vaccines in curtailing SARS-CoV-2 infection and disability leave utilisation among healthcare workers during the COVID-19 pandemic: cross-sectional analysis from a tertiary healthcare system in the Greater Houston metropolitan area - Vahidy, Farhaan S; Pan, Alan P; Hagan, Kobina; Bako, Abdulaziz T; Sostman, Henry Dirk; Schwartz, Roberta L; Phillips, Robert; Boom, Marc L (BMJ open, 2021)
ObjectivesWe provide an account of real-world effectiveness of COVID-19 vaccines among healthcare workers (HCWs) at a tertiary healthcare system and report trends in SARS-CoV-2 infections and subsequent utilisation of COVID-19-specific short-term disability leave (STDL).DesignCross-sectional study.Setting and participantsSummary data on 27 291 employees at a tertiary healthcare system in the Greater Houston metropolitan area between 15 December 2020 and 5 June 2021. The initial 12-week vaccination programme period (15 December 2020 to 6 March 2021) was defined as a rapid roll-out phase.Main outcomes and measuresAt the pandemic onset, HCW testing and surveillance was conducted where SARS-CoV-2-positive HCWs were offered STDL. Deidentified summary data of SARS-CoV-2 infections and STDL utilisation among HCWs were analysed. Prevaccination and postvaccination trends in SARS-CoV-2 positivity and STDL utilisation rates were evaluated.ResultsUpdated for 5 June 2021, 98.2% (n=26 791) of employees received a full or partial dose of one of the approved mRNA COVID-19 vaccines. The vaccination rate during the rapid roll-out phase was approximately 3700 doses/7 days. The overall mean weekly SARS-CoV-2 positivity rates among HCWs were significantly lower following vaccine roll-out (2.4%), compared with prevaccination period (11.8%, p<0.001). An accompanying 69.8% decline in STDL utilisation was also observed (315 to 95 weekly leaves). During the rapid roll-out phase, SARS-CoV-2 positivity rate among Houston Methodist HCWs declined by 84.3% (8.9% to 1.4% positivity rate), compared with a 54.7% (12.8% to 5.8% positivity rate) decline in the Houston metropolitan area.ConclusionDespite limited generalisability of regional hospital-based studies—where factors such as the emergence of viral variants and population-level vaccine penetrance may differ—accounts of robust HCW vaccination programmes provide important guidance for sustaining a critical resource to provide safe and effective care for patients with and without COVID-19 across healthcare systems.